The Application of Think Talk Write (TTW) Learning Model to Improve Students' Communication Skills - Dewiantika Antika Azizah; Indah Karina Yulina; Siti Fatonah; Tania Avianda Gusman (Jurnal Penelitian Pendidikan IPA, 2022)
Communication skills are one of the mandatory skills that students must master for the development of the 21st century. The use of innovative learning models can also help students to understand the concept of material. The purpose of this study was to improve the communication skills of class X SMK students on the material of the atomic structure and the periodic table of elements by using the Think Talk Write (TTW) learning model. The research subjects used were students of class X Pharmacy in the academic year 2022/2023. Research data used on communication skills through observation sheets and study documentation and for learning outcomes used through description tests for pretest and posttest. The data analysis used was quantitative with a quasi-experimental design research type. The results showed that there was an increase in communication skills through observation sheets with an average value of 80.96 in the high category and documentation studies with an average value of 73.21 including the high category. The use of the Discovery Learning model showed that the students' communication skills had increased with an average score of 76.44 on the observation sheet in the high category and the study of documentation with an average value of 70.12 was included in the high category. The conclusion was that the application of the Think Talk Write (TTW) learning model was more effective than the application of the Discovery Learning model, so the researchers recommend to use this learning model to help improve students' communication skills